PERENCANAAN SISTEM DRAINASE LINGKUNGAN KAWASAN LOLOAN TIMUR, KABUPATEN JEMBRANA - Mahayana, Ketut Hedi; Nuraga, I Ketut; Budiarnaya, Putu; Ariawan, Putu (Jurnal Ilmiah Telsinas, 2019)
Bali is one of the provinces in central Indonesia that is famous for the comfort of its area. Of course this must be supported by adequate infrastructure such as drainage. With the increasing number of residents in each area such as in Jembrana Regency and inadequate drainage facilities, causing floods that disrupt the comfort of the area, drainage planning, especially secondary and tertiary channels, is necessary. in urban areas. Therefore the drainage planning there is adjusted to the planning standards that have been set and planned with dimensions using a return period (5 years) for secondary or tertiary channels. The purpose of the Final Project is to find out the plans for the environmental drainage system and analyze the dimensions of the channel drainage that can overcome inundation in the East Loloan area, Jembrana Regency. Data used are rainfall data from 2007-2016, using the RAPS method, Thiesson Polygon, type III log pearson, Smirnov-Kolmogrov, Talbot and Rational methods, the method used until you get a plan debit with an average of 0.3275 m3 / sec. Continuing to calculate the dimensional recommendations with a hydraulics count using the principle of uniform flow. From the existing conditions in the East Loloan area, Jembrana Regency often experiences inundation because of the inadequate channel dimensions, therefore it is necessary to do a re-planning with dimensions that can accommodate a larger water discharge so that inundation does not occur as before with a count of planned new plans.